Body Mass Index and Working Period Associated with Low Back Pain in Pedicab Drivers - Amardeep Kaur Kaur Singh; Indri Seta Septadina; Eka Febri Zulissetiana (Health Science Journal of Indonesia, 2022)
Background: Low back pain (LBP), commonly referred to radiating low back pain or sciatica, is the discomfort between the ribcage and the gluteal folds. A risk factor for LBP is being overweight because weak abdominal muscles lead the center of gravity to shift forward, increasing lumbar lordosis and promoting exhaustion in the paravertebral muscles. A working period is an accumulation of one's work activities over a long period. If the activity is carried out continuously over the years can cause health problems. Methods: This study was an observational analytic study using a cross-sectional study—a research population of pedicab drivers in Kemuning District, Palembang City. Classification data include age, gender, and body mass index Results: Fifty-seven pedicab drivers met the requirements for participation. Bivariate analysis using the Chi-Square Test yielded a p-value of 0.038, indicating a significant association between BMI and low back pain, and a p-value of 0.025, indicating a significant association between length of employment and lower back pain. Conclusion: BMI and working period had a significant relationship with lower back pain. Keywords: low back pain, working period, body mass index Abstrak Latar Belakang :Nyeri Punggung Bawah (NPB) adalah nyeri di daerah punggung di antara tulang rusuk dan lipatan gluteal, termasuk juga nyeri ekstremitas yang menjalar karena gangguan punggung. Berat badan yang berlebih menyebabkan tonus otot abdomen lemah, sehingga pusat gravitasi seseorang akan terdorong ke depan dan menyebabkan lordosis lumbalis akan bertambah yang kemudian menimbulkan kelelahan pada otot paravertebra, hal ini merupakan risiko terjadinya LBP. Lama kerja merupakan akumulasi aktivitas kerja seseorang yang dilakukan dalam jangka waktu panjang yang apabila aktivitas tersebut dilakukan terus-menerus dalam jangka waktu bertahun-tahun dapat mengakibatkan gangguan kesehatan. Metode : Penelitian ini adalah penelitian analitik observasional dengan menggunakan rancangan potong lintang (cross-sectional study). Populasi penelitian pengayuh becak di Kec.Kemuning, Kota Palembang. Data klasifikasi meliputi usia, jenis kelamin, indeks massa tubuh. Ditemukan 57 pengayuh becak yang memenuhi kriteria inklusi. Hasil : Hasil analisis bivariat yang diperolehi dengan Uji Chi Square diperoleh nilai p sebesar 0.038, artinya terdapat hubungan yang signifikan antara IMT dengan nyeri punggung bawah dan nilai p sebesar 0.025 artinya terdapat hubungan yang signifikan antara lama kerja dengan nyeri punggung bawah. Kesimpulan : IMT dan lama kerja mempunyai hubungan yang signifikan dengan nyeri punggung bawah. Kata kunci: nyeri punggung bawah, usia, IMT